The performance of the finnish labour markets in the 1990s - Elli Heikkilä; Sirpa Korhonen (European Regional Science Association (ERSA), 2002)
The paper deals with performance of local labour markets in Finland. The gross-stream labour statistics provide useful tool for this analysis. The subject of the research is the working-aged population. The local labour markets are divided into three classes: major cities, regional centres and smaller centres. The periods of observation are years 1990-91 and 1996-97 in the stream data. During the former period Finland was sliding into depression, whilst in the latter period it was rising out of that same depression. Competence and know-how are important elements in regional development. They are intimately connected with the creation of, and accessibility to the high quality workforce needed by each region, as well as the in the general interest of the region as a whole, in particular with regard to the prospective location of profitable economic activities. Regional development is linked to migration and population development. Higher education and other institutions have proved to be important in population development.
Keywords: 330